Pelatihan Inovasi Kreasi Produk Dendeng Giling Daging Babi Sebagai Peluang Usaha Bersama Bagi Ibu-Ibu di Desa Wonorejo: Training on Innovative Creation of Ground Pork Jerky Products as a Joint Business Opportunity for Mothers in Wonorejo Village - Hari Minantyo (Jurnal Abdimas Pariwisata, 2024)
Training on Innovative Creation of Ground Pork Jerky Products as a Joint Business Opportunity for Mothers in Wonorejo Village, Bantur Subdistrict, Malang Regency. The purpose of conducting this community service initiative originates from the existing issues in Wonorejo Village, namely the abundance of pig livestock that has not been utilized to create a flagship village product. A group of mothers in business together in Wonorejo Village aims to innovate processed products from pig meat to achieve high economic value by producing ground pork jerky. The future expectation of this training is to provide knowledge to the mothers in the business group so that they can process pig meat into ground pork jerky as a high-quality processed product. The goal is to create a product with a longer shelf life that can be marketed as a souvenir from Wonorejo Village with high economic value. The training is conducted using three methods: socialization, technical guidance in the form of practical training, and evaluation. Socialization takes place for one day at the home of one of the residents in Wonorejo Village. Technical guidance and evaluation are conducted at the home of another resident, with the participation of 10 mother business groups in Wonorejo Village. The socialization covers innovative and creative methods of making ground pork jerky. The technical guidance includes the cooking process of ground pork jerky to ensure long shelf life and high economic value. The conclusion drawn from the evaluation results involving participants, organizers, and resource persons is the need for periodic training and real implementation in the field.